Plūk khon phư̄a plūk pā : plūk pā kǣ čhon (Mūnnithi Mǣfā Lūang, 2009)
On the role of Mae Fah Luang Foundation in implementing the permanent reforestation project for socio-economic development and poverty reduction in mountainous Thoet Thai Sub-district, Chiang Rai Province, Northern Thailand.